Energy production through microbial fuel cells (MFC's) using fish pond water and sediments taken from Pinamuk-an, New Washington, Aklan. - Regatalio, Rez (2011.)
Microbial fuel cells (MFCs) are devices that use bacteria as the catalysts to oxidize organic and inorganic and generate current. A two chambered MFC was used where there is an anode and a cathode chamber. it was cosntructed from accessible and inexpensive mataerials. There were three treatments that were carried out. First, only sediments concentrations were analyzed . Second is the MFC where bangus feeds were added to the sediments. The third treatment was bangus feeds and ammnium sulfate solutions were added to the sediments. Data were recorded and collected everydat for 25 days in the first and second treatments while only 14 days for the third treatment. The power density and the current density were then calculated for all treatments. The results of the present study show that MFC could be used to generate electricity using pond water sediments as substrate. The most efficient MFC was composed of 30 percent and 40 percent sediment alone for highest voltage and 30 percent sediment + bangus feed + ammonium sulfate for highest amperage.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Microbial Fuel Cells; Fish Pond Water